ZONASI TINGKAT KERENTANAN BANJIR DI KOTA BANJARBARU KALIMANTAN SELATAN - Enu Bahtiar Setiawan; Fadly Hairannoor Yusran; Fakhrur Razie; Rina Mustika (Universitas Lambung Mangkurat, 2015)
Zoning Level of Flood Susceptibility in Banjarbaru City, South Kalimantan. This research aims to formulate the control guide line of flood susceptibility in Banjarbaru, South Kalimantan Province. The goal is ac hieved through thest ages of study as follows: 1. Analyzing the characteristics of Banjarbaru City consisting of a) the use of land; b) rain fall; c) physical characteristics of land (infiltration); and d) on steepness, 2. Conducting the zoning level of flood susceptibility in Banjarbaru City, and 3.Producing a chart of flood susceptibility for Banjarbaru City. This research applies descriptive method that consists of data gathering, data processing and data analysis. Determining the high suspectibility of flood is done by weighting indicators of flood through the closing of land, the rain intensity, the physical characteristics of land (infiltration), and the tilt of slope. uper weighting, classification of flood susceptibility is carried out. Thecategory of level is done by multiplying variable values with the variable weight. Of fload susceptibilityis divided into four categories: very fragile, ,fragile, somewhat fragile, and not fragile. This research results flood susceptibility zoning level that aims to identify the areas that are fragile to flood, so this region can be analysed to prevent and handle flood. Based on the result of data collection ,data processing and data analysis, it can be concluded that: 1) based on the results of the analysis toward the flood susceptibility variable, it can be concluded that the cause of flood susceptibility in Banjarbaru City is the change in the landuse because it has great weight beside the topography of the area. Banjarbaru City also has the tilt tendency to beflat (0-8%), so the water from a higher place then will gather in this area. 2) Based on flood susceptibility zoning level in Banjarbaru City ,it is discovered that an area of 16,810 hectares or 51% of Banjarbaru City's width is located in the level of somewhat fragile, then an area of 13,118 hectares or 40% is not fragile and 3,156 hectares or 9% is fragile to flood. 3) The chart of fload susceptibility in Banjarbaru City has shown that almost all parts of areas in Banjarbaru City are zones with high flood susceptibility level with the criteria of not fragile ,somewhat fragile and fragile.